2009
DOI: 10.1111/j.1551-2916.2009.03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Growth of Vertical ZnO Nanorods

Abstract: Vertically aligned, single crystalline ZnO nanorods with a high packing density and diameter of B60 nm have been successfully synthesized via a low-temperature hydrothermal route on glass substrates pre-deposited with a ZnO seeding layer. The seeding layer exhibits an epitaxial effect on the growth and alignment of the ZnO nanorods. This epitaxial effect can arise from two considerations, namely the crystalline orientation and surface roughness of the seeding layer, which can be controlled by the curing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…The pattern contains mainly the [002] peak, which confirms the preferential growth direction of ZnO along the c-axis [17] and indicates that seeds with caxis orientation normal to the substrate will act as nucleation sites for the grown nanorods. Nevertheless, the average diameter of the nanorods is larger than the grains in the seed layer, indicating that different grains in the seed layer nucleate to allow for the growth of one nanorod, also observed by Lee et al [18] Recently, we showed that a 20-nmthick seed layer is the optimum for a hole blocking layer in hybrid solar cells. SEM analysis shows an average diameter around 60 and 100 nm for the ZnO nanorods grown on a seed layer of thickness 20 and 100 nm, respectively (Figure 2 b-e).…”
Section: Resultssupporting
confidence: 62%
“…The pattern contains mainly the [002] peak, which confirms the preferential growth direction of ZnO along the c-axis [17] and indicates that seeds with caxis orientation normal to the substrate will act as nucleation sites for the grown nanorods. Nevertheless, the average diameter of the nanorods is larger than the grains in the seed layer, indicating that different grains in the seed layer nucleate to allow for the growth of one nanorod, also observed by Lee et al [18] Recently, we showed that a 20-nmthick seed layer is the optimum for a hole blocking layer in hybrid solar cells. SEM analysis shows an average diameter around 60 and 100 nm for the ZnO nanorods grown on a seed layer of thickness 20 and 100 nm, respectively (Figure 2 b-e).…”
Section: Resultssupporting
confidence: 62%
“…From our previous experience, we understand that the surface morphology and texture of the seeding layer play a very important role in the growth alignment and texture development of ZnO nanorods, as it serves to provide a heterogeneous nucleation site for the growth of ZnO nanorods. 21 A poorly crystallized and randomly oriented seeding layer with high surface roughness yielded nanorods with a highly disarrayed alignment. In contrast, vertically aligned nanorods were obtained from smooth and highly crystallized ZnO seeding layers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nucleation mechanism of ZnO NRs on the seed layer has not yet been clearly understood. It has been proposed that ZnO NRs epitaxially grow on the polycrystalline ZnO seeds …”
Section: Discussionmentioning
confidence: 99%